Communication networks, externalities, and the price of information. (4th April 2019) - Polanski, Arnold
Abstract: Information goods (or information for short) play an essential role in modern economies. We consider a setup where information has some idiosyncratic value for each consumer, exerts externalities, and can be freely replicated and transmitted in a communication network. Prices paid for information are determined via the (asymmetric) Nash Bargaining Solution with endogenous disagreement points. This decentralized approach leads to unique prices and payoffs in any exogenous network. We use these payoffs to find connection structures that emerge under different externality regimes in pre‐trade network formation stage. An application to citation graphs results in eigenvector‐like measures of intellectual influence.